A world for us the case for phenomenalistic idealism - Foster, John, 1941 May 5- (Oxford : Oxford University Press, 2008)
'A World For Us' shows that the physical world does not exist independently of the human mind, but draws its existence from the way in which, under God's ordinance, things appear to us in experience.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Idealism; Realism; Phenomenology